WALTER BENJAMIN, LA INTELIGENCIA RADICAL - Ayala Saavedra, Roberto (2023)
This article builds on interpretative hypothesis about the historical-sociostructural and intellectual —conditions that made possible the irruption— between the world wars of the 20th Century —of the atypical and eccentric personality, life and work of Walter Benjamin. The author points to the neo-romantic elements present in his thought, as key to understand the complex configurations that led Ernst Bloch to qualify it as “a surrealist way of thinking” without doubt a flattering statement for his addressee.